An Inclusive Workplace Framework: Principles and Practices for Work-Integrated Learning Host Organizations - Fleming, Jennine; Hay, Kathryn (International Journal of Work-Integrated Learning, 2024)
Work-integrated learning (WIL), as an educational approach, is facilitated through relationships between Higher Education Institutions (HEIs) and external ‘host’ organizations. Responsible host organizations should recognize that students undertaking WIL come from a range of different cultures, socio-economic backgrounds, and have varying academic, physical, and other capabilities. An inclusive workplace will seek to facilitate a positive and rewarding experience for all WIL students. Recent WIL literature has seen a strong focus on inclusive access to WIL. This article examines key elements that can contribute to host organizations providing an inclusive environment for students. Socio-cultural theories related to learning in the workplace are used as a theoretical lens. An Inclusive WIL Workplace Framework is proposed, highlighting principles, practices, and supervisor and co-worker characteristics, that can be utilized by workplaces to assess their inclusivity and address any gaps, and by students to understand the expectations of HEIs on host organizations.
Keywords: Inclusion; host organizations; equity; Indigenous; diversity